Assessment of Occurrence of RAS in Children and its Association with Oral Hygiene (Medico Legal Update, 2020)
Objective: To assessing occurrence of minor recurrent aphthous stomatitis (RAS) in children and itsassociation with oral hygiene.Materials and Method: The present study was conducted on 428 school children of age ranged 6- 13years of both genders. Complete oral examination for assessment of decayed teeth, missing and filled teethand DMFT index was done. The data was analyzed using IBM SPSS Statistics for Windows, Version 22.0.Armonk, NY: IBM Corp with Chi square test.Results: In 291 (67.9%) cases, type of RAS was minor, in 85 (19.8%) major and in 52 (12.1%) herpetiform. Most common factors causing RAS in children was food stuffs in 210 (49%) followed by nutritionaldeficiency in 166(38.7%), stress in 38 (8.8%) and other factors in 14 (3.2%) patients. 312 (72.8%) patientshad dmft score >1, 97 (46.1%) patients had intolerance to milk products, 58 (27.6%) had intolerance to egg,20 (9.52%) to fish and 35 (16.6%) had to gluten. 102 (23.8%) patients had history of coelic disease in family.The difference was significant (P< 0.05).Conclusion: Recurrent aphthous stomatitis minor was most commonly occurring among children. Maximumnumber of patients had dmft score >1 and intolerance to food stuff.